2003
DOI: 10.1037/0022-006x.71.6.973
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Specificity in Psychotherapy: A Meta-Analysis of Structural Equivalence of Placebo Controls.

Abstract: Placebo treatments in psychotherapy cannot adequately control for all common factors, which thereby attenuates their effects vis-a-vis active treatments. In this study, the authors used meta-analytic procedures to test one possible factor contributing to the attenuation of effects: structural inequalities between placebo and active treatments. Structural aspects of the placebo included number and duration of sessions, training of therapist, format of therapy, and restriction of topics. Results indicate that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
278
1
16

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(299 citation statements)
references
References 43 publications
(53 reference statements)
4
278
1
16
Order By: Relevance
“…However, a close look at Table 1 indicates that the CBT ES generated in TADS is not characteristic of most CBT or psychotherapy effects on youth depression; 20 of the 23 other CBT programs in the table showed larger ES than the TADS version of CBT, and the mean ES value across the non-TADS CBT programs in the table was 0.48, markedly higher than the −0.07 ES associated with the TADS CBT intervention. What is not clear from the available data is whether this picture results from a low-potency version of CBT in TADS, from the unusual and challenging comparison of CBT with a medication placebo condition in TADS (see Baskin et al, 2003), from a combination of the two, or from other factors not identified. A concern raised by some (e.g., Jensen, 2003;Weisz, 2004) about the evidence on youth treatment research in general is that so many of the trials have compared active treatment with passive control conditions, including no treatment and waitlist.…”
Section: Discussionmentioning
confidence: 99%
“…However, a close look at Table 1 indicates that the CBT ES generated in TADS is not characteristic of most CBT or psychotherapy effects on youth depression; 20 of the 23 other CBT programs in the table showed larger ES than the TADS version of CBT, and the mean ES value across the non-TADS CBT programs in the table was 0.48, markedly higher than the −0.07 ES associated with the TADS CBT intervention. What is not clear from the available data is whether this picture results from a low-potency version of CBT in TADS, from the unusual and challenging comparison of CBT with a medication placebo condition in TADS (see Baskin et al, 2003), from a combination of the two, or from other factors not identified. A concern raised by some (e.g., Jensen, 2003;Weisz, 2004) about the evidence on youth treatment research in general is that so many of the trials have compared active treatment with passive control conditions, including no treatment and waitlist.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, for example, notably high pill placebo response rates are routinely found in depression-outcome research, averaging 30% to 40% and up to 70% (85). In a recent study (86), the authors concluded that outcome differences between putative active psychotherapies and placebo control conditions are neglible when the placebo condition is designed to be "structurally equivalent" (for example, matched on number and duration of therapy sessions and similar therapist training ) to the putative active treatment-which well illustrates the problem posed by placebo response.…”
Section: What Are the Causal Change Mechanisms Of Efficacious Psycholmentioning
confidence: 88%
“…(The above-mentioned Baskin and others [86] study addresses the question.) Two related questions are as follows:…”
Section: What Are the Causal Change Mechanisms Of Efficacious Psycholmentioning
confidence: 98%
“…Reviews of the controlled-trial psychotherapy research literature show that systematic matching is not a customary practice (Baskin, Tierney, Minami, & Wampold, 2003;Critelli & Neumann, 1984;Horvath, 1988;Stevens et al, 2000). Rather than precisely controlling for the common factors across psychotherapies, researchers typically use waiting lists, educationally focused groups, dissimilar comparative treatments, and treatment as usual for this purpose.…”
Section: Designing a Control For A Behavioral Group Therapymentioning
confidence: 99%
“…For example, defining structural equivalence by including the same number of sessions and treatment modality (e.g. group therapy, pharmacotherapy), Baskin et al (2003) found smaller effect size differences when active treatments were compared to structurally equivalent controls and larger effect size differences when controls were structurally inequivalent. Baskin and colleagues' focus on requiring equivalent modalities in their definition may explain why earlier studies (Bowers & Clum, 1988;Stevens et al, 2000) were unable to detect meaningful group differences.…”
Section: Designing a Control For A Behavioral Group Therapymentioning
confidence: 99%